ӨЗБЕКСТАНДА АЎЫЛ ХОЖАЛЫҒЫН БАСҚАРЫЎДЫ ЖӘҲӘН СТАНДАРТЫНА АЛЫП ШЫҒЫЎ БАСҚЫШЛАРЫ - Хожалепесов, П.З.; Зинатдинов, Д.П. (FAN va JAMIYAT, 2020)
This article shows the implementation of the cluster method in the agricultural sector. The article analyzes the growth of agricultural production.